Evaluation of menthol depressant activity in rainbow trout (Oncorhynchus mykiss) under different pH conditions - Urzúa, Natalia (2021)
The action of menthol on physiological and anesthesiological variables in rainbow trout was evaluated. Clinically healthy juvenile trout were used, of both sexes, formed in group A (n=20) of 201.4 ± 60.1 g of weight subjected to 100 ppm/L of menthol in water at pH 6.4 and in group B (n=20) of 187.3 ± 48.6 g of weight exposed to identical concentration of menthol with the water adjusted to pH 8.0 with sodium bicarbonate. The fish were placed in containers with water at 16.7 °C and electrical conductivity of 0.10 mS cm-1. The work methodology was: 1) acclimatization of fish in a container without drug and recording of the basal respiratory rate (RR) after adopting a normal swimming behavior; 2) transfer to a second container with menthol and recording of times of loss of lateral balance and anesthesia; 3) transfer of anesthetized fish to a third container without drug and record of RR and its behavior during the recovery period. In group A, anesthesia was achieved in 127.7 ± 46.3 s with a strong reduction in baseline RR from 132.4 ± 12.6 to 40.4 ± 14.4 mov/min and total recovery occurred in 189.7 ± 64.2 s. In group B, anesthesia and recovery time were observed at 93.4 ± 34.3 and 181.7 ± 68.0 s, respectively, and a reduction in RR from 137 ± 14.3 to 43.6 ± 10.4 mov/min. The results indicate that menthol in water adjusted to pH 8.0 is a good alternative for rainbow trout fish farming practices.